Vendor Business School Empowers Livelihoods in Philippines: Testimonies from Small Market vendors - CGIAR initiative on Resilient Cities (CGIAR System Organization, 2024)
The Vendor Business School (VBS) is an innovative approach for enhancing the entrepreneurial abilities and business practices of small food market sellers. In this video, hawkers and vendors from both public and private markets testify to the value of attending and finishing the VBS. The vendors emphasized the lessons they had learned about food safety, seasonality, customer relations, and record keeping which helps better their livelihood. In the Philippines, the CGIAR Resilient Cities Initiative VBS was implemented with the Quezon City government.